Merger of complements: Empirical evidence from the eyewear industry - Gaudin, Germain; Nagel, Niklas (International journal of industrial organization, 2025)
We analyze the effects of a merger between sellers of perfect complements in an oligopolistic industry. Relying on a unique dataset listing every pair of glasses sold by almost 400 independent opticians in Germany, we study the effects of the 2018 merger between the global leading producer of ophthalmic lenses and the global leading producer of eyewear frames. We show that the retail prices of components produced by the merging parties decreased with the merger, relatively to the prices of components produced by competing firms. This is, according to the theory, due to a reduction in double-marginalization resulting from the internalization of externalities after the merger. We also find that the relative price decrease is asymmetric across component markets, in line with our theory. •We evaluate the effects of a merger between sellers of complementary goods.•Theory predicts that prices of the merging parties' goods should decrease with the merger.•We find that prices of the merging parties' goods decrease after the merger, relatively to prices of competitors' goods.